STUDENTS' PERCEPTION OF FIRST LANGUAGE USAGE IN EFL CLASSROOM: A CASE OF SENIOR HIGH SCHOOL STUDENTS - Gina Larasaty; Atikah Wati; Roudlah Roudlah (Universitas Sarjanawiyata Tamansiswa, 2021)
This study investigated students' perceptions, students' attitudes, and students' main reasons for supporting first language use in the EFL classroom. A qualitative approach with a holistic-single case study design was applied, and the instruments were a Questionnaire and interview session. The participants were 22 students of grade XI from the Social Program at the MAN 1 Indramayu. The participants answered questions administered through 29 questionnaire statements and eight interview questions. The result showed that (1) the students rarely speak English during English learning in the EFL classroom, (2) The students strongly agree if the teacher uses First Language (L1) when explaining something complicated, like grammar or unfamiliar vocabulary. (3) The students' main reason that the students did not understand and still have doubts about some vocabulary. The interview result indicated that first Language (L1) is still needed in the EFL classroom.